Body Positivity in The Main Female Character in Sierra Burgess is A Loser (2018) Film - Rifa Afantia; Moh Supardi (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This research aims to explore the characterization of Sierra as the main female character reflecting body positivity presented in the Sierra Burgess Is a Loser (2018) film directed by Ian Samuels. This research uses the descriptive qualitative method supported by the character and characterization theory by Joseph M. Boggs and Dennis W. Petrie and representation theory by Stuart Hall. This research also uses the concept of body positivity by Tracy and Wood Barcalow to support the analysis. In the Sierra Burgess Is a Loser film, Sierra represents intelligence, independence, and confidence as a teenage girl who reflects body positivity. She struggles to achieve her freedom as a plus body size woman. Becasue of her plus body size, Sierra experiences injustice and bullying as a fat girl in her school. Sierra reflects body positivity as she fights to gain her confidence and face her fear through the struggles of being a fat girl. Moreover, it shows that Sierra Burgess Is a Loser (2018) film tries to support the body positivity movement as the film portrays Sierra as an intelligent woman who breaks the stereotype of unrealistic body image and manages to embrace other women to have a body positivity image.